80P Nintedanib (N) + docetaxel (D) after immunotherapy in adenocarcinoma non-small cell lung cancer (NSCLC): First results from the non-interventional LUME-BioNIS study. (15th December 2019) - Reck, M; Syrigos, K; Miliauskas, S; Zöchbauer-Müller, S; Buchner, H; Kitzing, T; Kerr, K M
Abstract: Background: N is an oral triple angiokinase inhibitor approved in 61 countries for use with D to treat locally advanced, metastatic or locally recurrent adenocarcinoma NSCLC after first-line chemotherapy (CT). Several immunotherapies are also now approved in various indications in advanced NSCLC, but limited data are available regarding outcomes with N + D after immunotherapy treatment. Methods: LUME-BioNIS is a European, prospective, multicentre, non-interventional study of patients (pts) with advanced adenocarcinoma NSCLC who initiated N + D after first-line CT in routine practice according to the approved N EU label. Information on dates of progression (based on clinical assessment or Response Evaluation Criteria in Solid Tumors) and death and adverse events (AEs) was collected via an electronic case report form. The primary endpoint was overall survival (OS). A subgroup analysis was conducted to evaluate outcomes in pts with prior immunotherapy. Results: In the 67 pts with prior immunotherapy, median age was 63 years and 27 pts (40.3%) were female. Prior immunotherapy was given in first line in 20 pts (29.9%) and in later lines in 47 pts (70.1%). The most common immunotherapies were nivolumab (39 pts; 58.2%), atezolizumab (13 pts; 19.4%) and pembrolizumab (11 pts; 16.4%). N + D was given in second line in 10 pts (14.9%) and in later lines in 57 pts (85.1%). Median progression-free survival (PFS) was 4.6 months (95% confidence interval [CI]: 3.5–5.7) and median OS was 8.8 months (95% CI: 7.0–11.5). In 65 pts evaluable for safety, the most common on-treatment AEs were malignant neoplasm progression (18 pts; 27.7%), diarrhoea (21 pts; 32.3%), nausea (10 pts; 15.4%) and vomiting (7 pts; 10.8%). Conclusion: Used according to the approved N label in routine practice, N + D showed clinically relevant effectiveness, with no unexpected safety findings, in pts with prior immunotherapy and CT. The observed median PFS and OS of 4.6 and 8.8 months, respectively, are encouraging, given the use of N + D in third or later lines in 85.1% of pts. These data add to the real-world evidence that can inform clinical decision-making in the changing therapeutic landscape. Clinical trial identification: NCT02671422. Editorial acknowledgement: Medical writing assistance, supported financially by Boehringer Ingelheim, was provided by Mark Dyson, DPhil (Berlin, Germany) on behalf of Syneos Health (London, UK). Legal entity responsible for the study: Boehringer Ingelheim Pharma GmbH & Co. KG. Funding: Boehringer Ingelheim Pharma GmbH & Co. KG. Disclosure: M. Reck: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: F. Hoffmann-La Roche; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Lilly; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: MSD; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Merck; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Novartis; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Celgene. K. Syrigos: Honoraria (self), Advisory / Consultancy: F. Hoffmann-La Roche; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy: MSD. S. Zöchbauer-Müller: Advisory / Consultancy, fees for participation in the LUME-BioNIS study: Boehringer Ingelheim; Advisory / Consultancy, Speaker Bureau / Expert testimony, fees for advisory boards and lectures: Boehringer Ingelheim; Advisory / Consultancy, Speaker Bureau / Expert testimony, fees for advisory boards and lectures: MSD; Advisory / Consultancy, Speaker Bureau / Expert testimony, fees for advisory boards and lectures: Bristol-Myers Squibb; Advisory / Consultancy, fees for advisory boards: Roche; Advisory / Consultancy, fees for advisory boards: AstraZeneca; Advisory / Consultancy, fees for advisory boards: Takeda; Speaker Bureau / Expert testimony, fees for lectures: Pfizer. H. Buchner: Research grant / Funding (self), former employee; received financial support for performing analyses during the conduct of the study: Boehringer Ingelheim Pharma GmbH & Co. KG. T. Kitzing: Full / Part-time employment, current employee of Boehringer Ingelheim Pharma GmbH & Co. KG: Boehringer Ingelheim Pharma GmbH & Co. KG. K.M. Kerr: Advisory / Consultancy, personal fees from Boehringer Ingelheim during the conduct of the LUME-BioNIS study: Boehringer Ingelheim. All other authors have declared no conflicts of interest.